Effects of Food, Gastric Acid Reduction, and Strong CYP3A Induction on the Pharmacokinetics of Tasurgratinib, a Novel Selective Fibroblast Growth Factor Receptor Inhibitor - Nomoto, Maiko; Hasunuma, Tomoko; Cai, Cuiyuan; Suzuki, Ippei; Mikubo, Ayano; Funasaka, Setsuo; Otake, Yohei; Nakai, Kenya; Yasuda, Sanae (Journal of clinical pharmacology, 2024)
We conducted this three‐part study in healthy subjects to investigate the pharmacokinetics of tasurgratinib (orally available selective inhibitor of fibroblast growth factor receptor 1‐3) and M2 (its major metabolite) under different conditions. In Part A, subjects received tasurgratinib 35 mg either fed with a high‐fat meal or fasted. In Parts B and C, subjects received tasurgratinib 35 mg alone or with either rabeprazole (acid‐reducing agent) 20 mg (Part B) or rifampin (strong CYP3A inducer) 600 mg (Part C). Primary endpoints were maximum concentration (Cmax), and areas under the plasma concentration‐time curve to time of last quantifiable concentration (AUC(0‐t)) and extrapolated to infinite time (AUC(0‐inf)). Forty‐two subjects were enrolled, 14 each into Parts A, B, and C. In Part A, administration of tasurgratinib with a high‐fat meal resulted in 33% reduction in Cmax and ∼23% reduction in AUC(0‐t) and AUC(0‐inf) of tasurgratinib, and 47% reduction in Cmax with ∼30% reduction in AUC(0‐t) and AUC(0‐inf) of M2. In Part B, co‐administration of rabeprazole at steady state resulted in no/weak interaction with tasurgratinib (∼8% increase in AUC(0‐t) and AUC(0‐inf) without an effect on Cmax) and M2 (∼18% increase in AUC(0‐t) and AUC(0‐inf) without an effect on Cmax). In Part C, co‐administration of rifampin at steady state resulted in a weak interaction with tasurgratinib (∼16% reduction in AUC(0‐t) and AUC(0‐inf)) and M2 (∼12% reduction in AUC(0‐t) and AUC(0‐inf)). Administration of tasurgratinib with a high‐fat meal appeared to reduce systemic exposure of tasurgratinib, however co‐administration with an acid‐reducing agent or a CYP3A inducer had a minimal impact on pharmacokinetics.